COMPARISON OF POLYMORPHISM rs2070672 CYP2E1 GENE PROPORTION IN EARLY AND ADVANCED STAGE OF UNDIFFERENTIATED TYPE NASOPHARYNGEAL CARCINOMA IN BALINESE - I Ketut Suanda; I Gde Ardika Nuaba; Ni Putu Ayu Wiarni Susanthi (TALENTA PUBLISHER, 2020)
Introduction: Nasopharyngeal carcinoma is the most common malignancy in the ENT field. The cause of nasopharyngeal carcinoma is multifactorial. One of the risk factors for an increase in nasopharyngeal carcinoma is the rs2070672 polymorphism of the CYP2E1gene. Purpose: To determine the rs2070672 CYP2E1gene polymorphism proportion in early and advanced stage undifferentiated type NPC subjects in Balinese. Method: This research is a cross sectional comparative study. The case population were all subjects with undifferentiated type NPC in the ENT outpatient clinic at Sanglah General Hospital Denpasar. This study uses 65 samples. Data collected in the form of subject characteristics and rs2070672 CYP2E1gene polymorphisms which examined by ARMS-PCR technique. Results: The average age of the sample was 48.1 years, the most were male as many as 48 subjects (73.8%), and the highest was advanced stage as many as 56 subjects (86.2%). In the chi square test the proportion of polymorphisms in the advanced stage was 2.357 times higher than the early stages. The results of multivariate analysis using logistic regression proved that the rs2070672 CYP2E1gene polymorphism at advanced stage was 7.469 times higher than early stage. Conclusion: There is a difference in the proportion of rs2070672 CYP2E1gene polymorphism in undifferentiated type NPC of Balinese, where advanced stage is higher than early stage.